Enhancing high school students’ understanding and skills in geophysical surveying and data processing: A service learning - Jumarang, Muhammad Ishak; Putra, Yoga Satria; Muliadi, Muliadi; Ihwan, Andi; Sampurno, Joko; Faryuni, Irfana Diah; Zulfian, Zulfian; Adriat, Riza; Perdana, Radhitya; Muhardi, Muhardi (Universitas Muhammadiyah Magelang, 2025)
Knowledge and skills in geophysical surveying and data processing are unique areas for high school students interested in environmental conditions. This community engagement activity aimed to enhance the understanding and skills of high school students in Pontianak City regarding geophysical surveying and data processing through direct field observations. The activity spanned five months, from June to October 2024, and included several stages: preparation, implementation, and evaluation. Evaluation was conducted with 41 participants, achieving a success index of 90.54%. These evaluation results indicate that the activity met the expectations of most participants. Key aspects such as participant satisfaction, program utility, material comprehension, presenter/facilitator delivery, and time allocation received very high appreciation from the participants.